Chemical and physical pressure effects in the A-site spinel antiferromagnets CoM2O4 (M = Al, Co, and Rh). (20th May 2020) - Naka, T; Valenta, J; Kaštil, J; Míšek, M; Prchal, J; Sechovský, V; Abe, H; Nakane, T; Nakayama, M; Uchikoshi, T
Abstract: Magnetic phase transitions under high pressure are reported for the diamond lattice antiferromagnet Co3−x Rhx O4 in the range of 0 ≤  x  ≤ 2.0, which is an isostructural S  = 3/2 system for the well-known frustrated antiferromagnet CoAl2 O4 . In the Co3−x Rhx O4 system, magnetic and specific-heat measurements at ambient pressure revealed that a second-order antiferromagnetic transition occurred at the Néel temperature ( T N ) which exhibits a nonmonotonic x -variation. The physical pressure variations of T N were determined by ac-calorimetry under hydrostatic pressures up to p  = 2.6 GPa for Co2 RhO4 and CoRh2 O4 . The rates of change of T N with pressure (i.e., the pressure coefficients), 1.93 and 1.61 K GPa −1, respectively, were comparable to those for CoAl2 O4 and Co3 O4, respectively. The pressure coefficients of magnetic ordering temperature for these A-site spinel compounds were considerably larger than those for other spinel and iron-garnet compounds which follow the empirical '10/3 law'. Simple analysis of the chemical and physical pressure coefficients of T N revealed that T N depended on both the lattice volume and the oxygen positional parameter u .